Pozycja tłumacza w postępowaniu cywilnym - Manikowski, Filip (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
W artykule omówiono prawa i obowiązki procesowe tłumacza w postępowaniu cywilnym. Ustalono, że tłumacz pełni bardzo ważną rolę w postępowaniu cywilnym, co oznacza, że niezbędne jest ustalenie – w sposób niebudzący wątpliwości – jego praw i obowiązków procesowych. To odpowiednie stosowanie przepisów powinno zapewnić przede wszystkim zachowanie przez tłumacza bezstronności oraz profesjonalizmu. Przyjęto, że gwarantem tego jest odpowiednie stosowanie do tłumaczy przepisów o biegłych.

The article discusses the procedural rights and obligations of a translator in civil proceedings. It has been established that translator plays a very important role in civil proceedings, which means that it is necessary to establish – beyond any doubt – his rights and procedural obligations. This appropriate application of the provisions should ensure, above all, that translator maintains impartiality and professionalism. The assumption was made that it is guaranteed by an appropriate application of the provisions on expert witnesses to translators.
Translation’s status in civil proceedings
Keywords: postępowanie cywilne; tłumacz; civil proceedings; translator